Analisis dan Perancangan UI/UX dengan Metode User Centered Design pada Website DLU Ferry - Cavanaugh, Alif Bimananda; Rahmawati, Endra; Putra, I Gusti Ngurah Alit Widana (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
In order to achieve the company's business objectives, namely the distribution of sea transportation between islands throughout Indonesia and contribute economically and socially to the country and include the wider community with middle to lower economic class. PT Dharma Lautan Utama provides the DLU Ferry website with the address tiket.dlu.co.id. Based on the results of interviews with the IT/EDP Division and supported by the results of questionnaires based on the System Usability Scale (SUS) method for customers, it is known that the DLU Ferry website has a "Good" rating with a score of 52.3. From these results, an evaluation and design of a new website display was carried out to improve usability by using the User Centered Design (UCD) method. The design process uses a wireframe and produces a prototype. The results of the UI/UX design have succeeded in producing 6 main needs, namely the home page, login, account registration, ticket reservation, my order, and profile. The initial and final evaluation uses a usability scale system with the calculation of the SUS score, the color scheme for the prototype display is inspired by the basic colors of the PT DLU logo, namely blue, light blue, and red. For the contents of the content, menus, and buttons use the â€œMulishâ€ font, while for the motto text use the â€œSarinaâ€ font. The results of the design are then carried out a final evaluation to determine the increase in website usability with an average SUS score of 82.7 with an "Excellent" rating, which means that the website looks better and meets customer needs.